A review of stochastic live load models for code calibration - ICASP14; Costa, Luis; Beck, André (My University, 2023)
Reliability-based calibration of partial safety factors of structural design codes requires suitable stochastic models for, among others, live loads. These models need to be compatible with the design values and exceedance probabilities stated in the same codes. This paper presents a critical review of the literature on stochastic models for live loads. These models consist of a sum of sustained and extraordinary loads, modelled as Poisson rectangular wave and spike processes, respectively. The models and their input parameters are reviewed by comparison to design values of EN 1991-1-1 and ASCE/SEI 7 codes. The main conclusion is that JCSS Probabilistic Model Code parameters are often too conservative and unrealistic. An overview of some live load statistics used in code calibration is also presented, and new statistics derived using Monte Carlo simulation are proposed. This study should be relevant for the development of Eurocodes, as its exceedance probabilities for design live loads are not clear.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED